Exploration of Community Acceptance in Greater Jakarta Towards All Gender Facilities: Use of Toilets and Changing Rooms - Angel Kurniawan; Arhoni Dachi; Niyu Niyu (Publikasi Indonesia, 2025)
The concept of All Gender Facilities has sparked controversy in many countries, particularly due to user concerns about the presence of other genders in private spaces such as changing rooms. This study aims to explore the acceptance of All Gender Facilities among Jabodetabek residents, focusing on their use in toilets and changing rooms. Employing a qualitative approach with a case study method, the research seeks to understand and analyze public responses influenced by social and cultural norms. Data were collected through in-depth interviews with eight purposively selected informants. The findings reveal that awareness and initial experiences with All Gender Facilities are shaped by media exposure and personal experiences when using such facilities. Security and cleanliness, encompassing the design and management of the space, are key factors influencing user privacy and comfort. Cultural norms significantly impact the acceptance of All Gender Facilities, emphasizing their role in societal resistance or approval. Support and neutrality toward All Gender Facilities are conditional, reflecting varying perspectives. The multicultural community in Jabodetabek demonstrates resistance to All Gender Facilities based on cultural and religious considerations, yet from a functional standpoint, these facilities are seen as acceptable.